Effects Of Hydraulic Loading Rates On Sewage Treatment Efficiency Of Constructed Wetlands - Zakaria, Fiona (2006)
Constructed wetlands have been used as an alternative option to treat wastewater. The adaptation of natural system has attracted researchers to use it considering its many advantages of environment friendly, cost and energy saving. Constructed wetlands have also been introduced in Malaysia, but since it is a new development, more studies should be carried out to support its implementation to suit Malaysian condition. In this study, a functional pilot scale of constructed wetlands to treat domestic wastewater was designed and constructed. The main objective of the study is to determine the effect of different hydraulic loading rates (HLRs) on the treatment efficiency. Wetlands were designed and constructed inside the engineering complex, Faculty of Engineering, UPM. There are three cells of constructed wetlands, all built in equal dimension, two cells were planted with Lepironia articulata, an indigenous Malaysia aquatic plant, known to be capable to remove pollutant from water, while one cell left unplanted to investigate the role of the plant in treatment process. Those cells were operated at four different HLRs in 2 phases e.g. 32, 16, 5.33 and 2.29 cm3/cm2/d which corresponding to hydraulic retention time (HRT) of 0.5, 1, 3 and 7 days respectively. Influent and effluent from each cell were then brought to laboratory to be tested. Parameters tested are pH, temperature, chemical oxygen demand (COD), total suspended solid (TSS), total phosphorous (TP), total ammonia nitrogen (TAN), nitrate, nitrite, total inorganic nitrogen (TIN), total coliforms, cadmium, copper, nickel, lead and zinc. The results show overall removal rates of 50.18 to 88.49% for TSS, 56.77 to 77.62% for COD, 39.67 to 88.68% for TP, 27.50 to 98.79% for TAN, 27.23 to 96.34% for TIN and 3 to 4 orders of magnitude for total coliforms. It was found that HLR has significant effect on removal of COD, TP, TAN and TIN, while the existence of plant only has effect on nitrogen removal, and TP when it was set at long retention time in Phase 2 (3 days). Effluents from constructed wetlands met requirements of Standard A of discharge standard for Malaysia, meaning that the effluents were safe to be discharged to any inland waters.